Simulations of Beam Quality in a 13 MeV PET Cyclotron - A. Pramudita; E. Mulyani; I.A. Kudus (PPIKSN-BATAN, 2015)
Simulation of the trajectories of negative hydrogen ion (H−) beam in a 13 MeV PET cyclotron (DECY-13) were carried out by using the Runge-Kutta (RK4) approximation method and Scilab 5.4.1. The magnetic and electric fields were calculated using Opera-3d/TOSCA softwares at 1 mm resolution. The cyclotron is of a fourth-harmonics type, meaning that the acceleration occurs four times per cycle, with a radiofrequency (RF) field of 77.66 MHz frequency and 40 kV amplitude. The calculations and simulations show that the maximum distance between the ion source and the puller is about 6 mm, while the maximum width of the beam at 13 MeV is about 10 mm, and the initial phase between the RF field and the beam ranges from -10° to 10°, with a yield of about 10% of the beam from the ion source getting accelerated to 13 MeV.Received: 12 March 2015; Revised:30 June 2015; Accepted: 01 July 2015